E.U. and China trends in trade in challenging times - Irena Jindřichovská; Erginbay Uğurlu (Journal of Risk and Financial Management, 2021)
The sudden and abrupt rise of COVID-19 became a challenge for the world economy. In this paper, we investigate the changes in a trend of mutual trade between the EU-15 countries and China during the demanding times of the COVID-19 crisis. We use monthly data for Chinese exports to the E.U. (2018:01-2020:05) and imports from the E.U. (2018:01-2020:07) relying on the data from the open-source TradeMap developed by the International Trade Centre UNCTAD/WTO (ITC). Overall, there is an obvious decline of 13-32 percent in worldwide trade as predicted by the WTO. This affected China as the main trading partner of electronic devices and medical supplies. The trade between the E.U. and China has decreased, but the major change in demand brought an alteration in commodities structures and the reorientation of Chinese export production. In the first five months of 2020, we witnessed the strong engagement of the Chinese economy in the production of goods newly in high demand-mainly articles strongly related to healthcare and medical equipment. Thus, we have observed that the Chinese were very flexible in changing the structure of their exports triggered by the COVID-19 crisis. This flexibility is worth further exploration, especially because the COVID-19 crisis is still not over and new data and changing results can be expected.
Keywords: 330; export; China; E.U.; import; international trade; the flexibility of production